Direct and indirect effects of weather experiences on life satisfaction: Which role for climate change expectations? - Daniel Osberghaus; Jan Kühling (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper deals with the effect of (i) damage experience from extreme weather events and (ii) expectations concerning future climate change on subjective wellbeing (SWB). We use data of a large representative survey amongst German households. The effect of experienced weather events on SWB of the heads of the households is only significant for heat waves; not for storms, heavy rain, and floods. Concern about future climate change on the household level has a substantial negative impact on current SWB. Moreover, we divide the impact of experience into direct effects of damage and indirect effects, which affect current SWB via the channel of expectations regarding future climate change. Both direct and indirect effects of weather experiences are quantified. It becomes apparent that the indirect effect is significant but small compared to the direct effect.
urn:nbn:de:bsz:180-madoc-369041
Keywords: Q54; Q51; D03; 330; climate change; subjective well-being; extreme weather events; household survey